Al-doped ZnO Thin Films via Sputtering: Influence of Structural Defects on Ozone Gas Sensitivity - Sales, Douglas Henrique [UNESP]; Leite, Ramon Resende; Albornoz Diaz, Julio Cesar Camilo; Komorizono, Amanda Akemy; Basso Bernardi, Maria Ines; Mastelaro, Valmor Roberto; Longo, Elson; Teixeira, Silvio Rainho [UNESP]; de Souza, Agda Eunice [UNESP] (FapUNIFESP (SciELO), 2024)
Nowadays, few studies have reported on the sensitivity of thin films of Al-doped ZnO to ozone. This gas can become harmful to health depending on its environmental concentration. This work presents the sensor response to ozone gas of pure ZnO and Al-doped thin films, prepared by sputtering with varying deposition times. Ceramic targets prepared by SSR, compacted at 65MPa, sintered at 950°C, with densities ranging from 74-97% of the theoretical density, depending on the dopant content were used. The films showed an increase in thickness with deposition time and a preferential growth in the (002) plane of the ZnO structure. Slight changes in the band gap value occurred with increasing Al, whose presence in the ZnO lattice was confirmed by XPS. The sensitivity results to ozone showed that the performance of the films decreased with the Al-doping, which could be attributed to the defects formation related to oxygen in the lattice during Zn-Al substitution or to the greater densification of the films. Although the results showed a decrease in the sensor properties, all films are sensitive to ozone, including the low concentrations of 50 ppb, a limit considered for a maximum daily average for human exposure, established by the WHO.
Keywords: ceramic targets; ozone; sensors; sputtering; thin films; ZnO